MAKING LEARNING VIDEOS FOR TEACHERS IN SUNDAY SCHOOLS - Natalia Tri Astuti; Nurul Frijuniarsi (Universitas PGRI Sumatera Barat, 2022)
The COVID-19 pandemic that has occurred in the last two years has become a big challenge for teachers, not only teachers in formal school education, but also for teachers in non-formal education, one of which is Sunday school. Many do not realize that Sunday schools have also been severely affected by this pandemic, where Sunday school children cannot worship directly, cannot do various events directly and cannot listen to stories to the fullest due to limited media. So, it is very difficult to understand the story or material delivered by their teacher. In this case, teacher competence and parental support are very influential on the development of every Sunday school child. In this case, measuring the success of learning can be seen from the child's ability to accept the material presented boldly. Therefore, children need to have high motivation and enthusiasm in participating in distance learning (PJJ) and teachers need to provide interesting and innovative learning media. Video as a learning media is considered to be very effective for use in both formal and informal education for children from kindergarten to elementary school. by utilizing video media which is considered to be able to increase children's motivation and enthusiasm for learning, so that it affects children's learning outcomes. Overall, it can be expected that this activity can achieve its goal, namely making videos that can increase motivation and attract children's learning interest.